185k views
4 votes
Find the derivative of f(x) = negative 6 divided by x at x = 12.

User Ella Ryan
by
6.3k points

2 Answers

0 votes

Answer:

1/24

Explanation:


f(x)=(-6)/(x)

We want to find the derivative of f at x=12.

I'm assuming you want to see the formal definition of a derivative approach.

The definition is there:


f'(x)=\lim_(h \rightarrow 0)(f(x+h)-f(x))/(h)

So we need to find f(x+h) given f(x).

To do this all you have to is replace old input, x, with new input, (x+h).

Let's do that:


f(x+h)=(-6)/(x+h).

Let's go to the definition now:


f'(x)=\lim_(h \rightarrow 0)(f(x+h)-f(x))/(h)


f'(x)=\lim_(h \rightarrow 0)((-6)/(x+h)-(-6)/(x))/(h)

Multiply top and bottom by the least common multiple the denominators of the mini-fractions. That is, we are going to multiply top and bottom by x(x+h):


f'(x)=\lim_(h \rightarrow 0)((-6)/(x+h)x(x+h)-(-6)/(x)x(x+h))/(hx(x+h))

Let's cancel the (x+h)'s in the first mini-fraction.

We will also cancel the (x)'s in the second-mini-fraction.


f'(x)=\lim_(h \rightarrow 0)(-6x--6(x+h))/(hx(x+h))

--=+ so I'm rewriting that part:


f'(x)=\lim_(h \rightarrow 0)(-6x+6(x+h))/(hx(x+h))

Distribute (NOT ON BOTTOM!):


f'(x)=\lim_(h \rightarrow 0)(-6x+6x+6h)/(hx(x+h))

Simplify the top (-6x+6x=0):


f'(x)=\lim_(h \rightarrow 0)(6h)/(hx(x+h))

Simplify the fraction (h/h=1):


f'(x)=\lim_(h \rightarrow 0)(6)/(x(x+h))

Now you can plug in 0 for h because it doesn't give you 0/0:


(6)/(x(x+0))


(6)/(x^2)


f'(x)=(6)/(x^2)

We want to evaluated the derivative at x=12 so replace x with 12:


f'(12)=(6)/(12^2)


f'(12)=(6)/(144)

Divide top and bottom by 6:


f'(12)=(1)/(24)

User Joel G Mathew
by
5.2k points
3 votes

Answer:

1/24

Explanation:

f(x) = -6/x

I will rewrite this as

f(x) = -6 x^-1

We know the derivative of x^-1 is -1 x^ (-1-1) or -1 x^-2

df/dx = -6 * -1 x ^ -2

df/dx = 6 x^-2

df/dx = 6/x^2

Evaluated at x=12

df/dx = 6/12^2

=6/144

=1/24

User LaszloLadanyi
by
5.5k points